Community Empowerment Through the PKK Program in Ilangata Village, Anggrek District, North Gorontalo Regency - Lisda Van Gobel; Irma Dumbela; Tety Thalib (Formosa Journal of Applied Sciences, 2023)
This study aims to determine Community Empowerment Through the PKK Program in Ilangata Village, Anggrek District, North Gorontalo Regency. This research consists of three focuses, namely the budget, socialization, and participation. The research method used is descriptive qualitative. The results of the study concluded that the budget funds owned by the PKK group were not optimal. This can be seen from the minimum budget for the PKK Program which does not reach 10 percent. Socialization of community empowerment by the PKK group has not been optimal. This can be seen from the lack of socialization activities carried out by the PKK in order to invite the community to participate in empowerment activities. The participation of the ilangata community in the community empowerment program implemented by the PKK is still very low. This can be seen from the minimal number of people, especially women who participate in community empowerment activities or programs. It is suggested that more active efforts are needed to succeed in community empowerment through the PKK program in Ilangata Village, Anggrek District, Gorontalo Regency by optimizing budget management, increasing socialization activities and fostering a caring attitude for the community to actively participate in community empowerment programs.